Aplikasi Pencari Lokasi Ukm Di Tembalang Menggunakan Location Based Service - Iqoniyoma Faundra; Rinta Kridalukmana; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2016)
SMEs (Small-Medium Enterprises) is one of the economical meters in Indonesia. Research step in designing the application is to determine main problem and purpose, analysis which covering general description, functional and non-functional need. Android base application to search UKM Tembalang which made for searching SMEs location, and give more information about SMEs business. UKM Tembalang is a client-server based application which made by using java programing language with eclipse software and MySQL database. Location data will be saved in database which focusing on taking coordinates that use GPS to get map and Google Maps APIs for getting the route. The use of Google Maps API service and GPS make the application better in taking the location coordinate. besides that, the application also get for searching position SMEs in Tembalang, with the application location searching SMEs.